2007
DOI: 10.1002/nme.2095
|View full text |Cite
|
Sign up to set email alerts
|

An element‐wise, locally conservative Galerkin (LCG) method for solving diffusion and convection–diffusion problems

Abstract: SUMMARYAn element-wise locally conservative Galerkin (LCG) method is employed to solve the conservation equations of diffusion and convection-diffusion. This approach allows the system of simultaneous equations to be solved over each element. Thus, the traditional assembly of elemental contributions into a global matrix system is avoided. This simplifies the calculation procedure over the standard global (continuous) Galerkin method, in addition to explicitly establishing element-wise flux conservation. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The LCG method is a technique introduced by Thomas and Nithiarasu [45][46][47], which treats each element as a sub-domain with its own boundaries. In this case, Equation (51) is expressed over an elemental sub-domain ( e ):…”
Section: Locally Conservative Taylor-galerkin Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The LCG method is a technique introduced by Thomas and Nithiarasu [45][46][47], which treats each element as a sub-domain with its own boundaries. In this case, Equation (51) is expressed over an elemental sub-domain ( e ):…”
Section: Locally Conservative Taylor-galerkin Methodsmentioning
confidence: 99%
“…Information is transmitted between elements via the flux term that is imposed as a Neumann boundary condition. It can be shown that the LCG method is equivalent to the global Galerkin method for convection-diffusion-type problems except on global boundaries [45]. One advantage of LCG method is that only small equations need to be solved; for 1D problems, the 2×2 matrices can be evaluated directly before coding, which removes the need for any matrix inversions.…”
Section: Locally Conservative Taylor-galerkin Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, Equations (4)- (6) are discretized in space using the LCG finite element method [31,33]. As with the global Galerkin form, the variation of each of the variables is approximated by the standard finite element spatial discretization as u i ≈ũ i = Nu i and p ≈p = Np where N are the shape functions.…”
Section: Lcg Spatial Discretizationmentioning
confidence: 99%